A four-wave survey to test the relative importance of schemas and metacognitive beliefs as within-person correlates of depressive symptoms - Cano-López, Julia B.; Nordahl, Henrik; García-Sancho, Esperanza; Anyan, Frederick; Salguero-Noguera, José Martín (Elsevier, 2026)
Understanding theorized psychological mechanisms underlying depressive symptoms at the within-person level can have direct implications for how depression is formulated and targeted in therapy. The cognitive model of depression postulates schemas as central mechanisms in depression, while the metacognitive model challenges this and emphasize dysfunctional metacognitive beliefs. Previous research has investigated the relative importance of these different belief domains in depression but have in large relied on cross-sectional data or focused on between-person prospective relationships. We aimed to evaluate the relative contribution of schemas versus metacognitive beliefs to depressive symptoms at the within-person level over a four-wave survey period (with 4- week intervals) in a sample of 526 individuals. Our results showed that change in positive metacognitive beliefs and negative metacognitive beliefs about the uncontrollability of rumination, but not change in schemas, were the unique factors associated with changes in depressive symptoms over time. Moreover, change in negative metacognitive beliefs about the social consequences of rumination was significantly associated with change in schemas above and beyond the change in depressive symptoms. Our findings suggest a more relevant contribution of metacognitive beliefs than schemas to depressive symptoms at the within-person level. Clinical implications and future directions are discussed, stressing the importance of replicating these findings in clinical samples.
Keywords: Psicología clínica; Depresión mental; schemas; metacognitive beliefs; depression; multi-level model; withinperson.